大功率调速型液力偶合器复合调节系统设计 - 张海军; 刘忠明; 张志宏; 李泉伟 (Jixie chuandong)
The speed control system for high power variable speed hydraulic coupling is studied,and the importance of the speed regulation characteristic linearization is pointed out.The mathematical model of speed ratio,the displacement of scoop tube,working oil and inlet area is set up,and the corresponding relation of speed ratio,working oil and inlet area is obtained.A design method of inlet&outlet compound regulating speed system is given,and the design method of oil inlet shape of valve and groove shape of scoop tube are introduced.